Herpes zoster of trigeminal nerve after dental extraction - Nagappa Guttiganur; Archana Devanoorkar; Shivanand Aspalli; Sudhir Shetty (Wolters Kluwer Medknow Publications, 2013)
Herpes zoster is an uncommon acute viral infection caused by reactivation of varicella zoster virus. During the prodromal stage, the only presenting symptom may be odontalgia, which may prove to be a diagnostic challenge for the dentist. Practicing dentist may carry out emergency treatment that might result in irreversible damage or may delay the appropriate treatment. With an ever-increasing number of elderly and immunocompromised patients reporting to the dentist, the dental profession can expect to encounter an increased number of herpes zoster patients. Dentist must be familiar with the presenting signs and symptoms of patients experiencing the prodromal manifestations of herpes zoster of the trigeminal nerve. This article focuses on the difficulties in management of such cases, and one such case is reported here.